Diabetic ketoacidosis in juvenile rats is associated with reactive gliosis and activation of microglia in the hippocampus. Issue 2 (16th January 2015) - Lo, Weei; O'Donnell, Martha; Tancredi, Daniel; Orgain, Myra; Glaser, Nicole
Abstract : Background: Type 1 diabetes may be associated with structural and functional alterations in the brain. The role of diabetic ketoacidosis (DKA) in causing these alterations has not been well explored. Methods: We used immunohistochemical staining to investigate cellular alterations in brain specimens from juvenile rats with DKA before, during, and after treatment with insulin and saline, and compared these to samples from diabetic rats and normal controls. Results: Glial fibrillary acidic protein (GFAP) staining intensity was increased in the hippocampus during DKA and increased further during insulin/saline treatment. Twenty‐four and 72 h after treatment, hippocampal GFAP intensity declined but remained above control levels. There were no significant changes in GFAP intensity in the cortex or striatum. OX42 staining intensity was increased during untreated DKA and increased further during insulin/saline treatment in the hippocampus and cortex. NeuN staining intensity was decreased after DKA treatment in the striatum but not in other regions. Conclusions: DKA causes inflammatory changes in the brain including reactive gliosis and activation of microglia. These findings are present during untreated DKA, but intensify during insulin/saline treatment. The hippocampus was disproportionately affected, consistent with previous studies showing deficits in hippocampal functions in rats after DKA recovery and decreased memory capacity in children with a history of DKA.